MATHEMATICAL MODELING OF ENGINEERING PRODUCTION VOLUME DEPENDENCE ON IRON ORE EXTRACTION - Maiborodina, N. V.; Gerasymenko, V. P. (Systems and Technologies, 2025)
Engineering is a key and strategically important sector of the Ukrainian economy, despite significant challenges, especially those associated with the full-scale war. This sector possesses considerable production and scientific-technical potential. This article examines the development a mathematical model for forecasting and analyzing the volume realized output of the engineering complex enterprises, based on the volume of iron ore mining in Ukraine. When creating an economic model or forecast, it is not necessary to consider the entire multitude of factors influencing the studied indicator. The key task is the filtering and selection a limited number of factors that exert the highest degree of influence. These dominant factors form the basis for reliable analysis, while the impact of secondary factors can be legitimately omitted. In this work, the volume of iron ore mining was chosen as the dominant factor affecting the volume the realized engineering output. For modeling the dependence realized engineering output volume in Ukraine, statistical data from the State Statistics Service of Ukraine and regression analysis methods were utilized. The model was developed using the Excel spreadsheet processor to automate the construction, analysis, and forecasting process based on the chosen model. The study includes the calculation of confidence intervals for the forecasted values the realized output volume of the Ukrainian engineering complex for the year 2026. To ensure the reliability the obtained forecasted values, the regression line with the highest approximation coefficient was selected. The research fully complies with the requirements of mathematical modeling: from setting the problem and selecting the key indicator to constructing, analyzing the model, and applying the results for forecasting the realized output volume of the Ukrainian engineering complex for 2026.